Influence of Logistics Service Quality, Delivery Reliability, and Price on Customer Satisfaction with Customer Service as Mediator and Logistic Service Recovery as Moderator in Freight Forwarding Industry - Iksan Ade Kurniawan; Melia Eka Lestiani; Maniah Maniah (Green Publisher Indonesia, 2026)
The growing competition in the logistics industry, particularly in freight forwarding, requires companies to deliver superior services that meet customer needs and expectations. This research aims to assess the conditions of Logistics Service Quality, Delivery Reliability, Price, Customer Service, Logistic Service Recovery, and Customer Satisfaction at PT Silkargo; analyze the effects of Logistics Service Quality, Delivery Reliability, and Price on Customer Satisfaction; examine the mediating role of Customer Service; and evaluate the moderating role of Logistic Service Recovery in the proposed research model. A quantitative explanatory design was applied using purposive sampling to collect responses from PT Silkargo customers. Data were obtained through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct, mediating, and moderating relationships among variables. The results show that Logistics Service Quality, Delivery Reliability, and Price significantly influence Customer Satisfaction, while Customer Service significantly mediates the relationships between those antecedents and Customer Satisfaction. Logistic Service Recovery significantly moderates the relationships between Logistics Service Quality and Customer Satisfaction, as well as between Price and Customer Satisfaction, but does not significantly moderate the relationship between Delivery Reliability and Customer Satisfaction. These findings indicate that, in the context of B2B lubricant distribution, customer satisfaction is threshold-based, where reliability and service quality function as necessary conditions rather than sources of competitive advantage.